SYMBOLIC DIMENSIONS OF PRESEAN AND THEIR ROLE IN THE INTERNALISATION OF PANCASILA VALUES IN SOCIAL EDUCATION - I Nyoman Miyarta Yasa; Galih Suryadmaja; Dewi Puspita Ningsih; Retno Utari; Ashar Banyu Lazuardi (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
The internalisation of Pancasila values among sociology education students often lacks contextual relevance to local culture. One potential approach is through the values of Presean culture, which can enhance the teaching of Pancasila ideology. The aim of this study is to analyse the role of internalising Presean cultural values in social learning and its impact on strengthening Pancasila ideology among sociology education students. The research methodology employed is a qualitative approach, utilising data collection techniques such as interviews, observations, and document studies. Analysis is conducted using a descriptive-interpretative approach to explore the meanings and impacts of Presean culture within the context of Pancasila education. The findings indicate that the internalisation of Presean cultural values, such as courage, sportsmanship, and adherence to rules, significantly contributes to enhancing students' understanding of the principles of Pancasila. Furthermore, this culturally-based learning has successfully raised students’ awareness of the importance of unity, social justice, and respect for human rights. Therefore, the integration of Presean cultural values into social education can serve as an effective alternative for strengthening Pancasila ideology among the younger generation.